Metformin Attenuates Silica-Induced Pulmonary Fibrosis by Activating Autophagy via the AMPK-mTOR Signaling Pathway - Li, Shu-xian; Li, Chao; Pang, Xin-ru; Zhang, Juan; Yu, Gong-chang; Yeo, Abrey J.; Lavin, Martin F.; Shao, Hua; Jia, Qiang; Peng, Cheng (Frontiers in Pharmacology, 2021)
Long-term exposure to crystalline silica particles leads to silicosis characterized by persistent inflammation and progressive fibrosis in the lung. So far, there is no specific treatment to cure the disease other than supportive care. In this study, we examined the effects of metformin, a prescribed drug for type Ⅱ diabetes on silicosis and explored the possible mechanisms in an established rat silicosis model in vivo, and an in vitro co-cultured model containing human macrophages cells (THP-1) and human bronchial epithelial cells (HBEC). Our results showed that metformin significantly alleviated the inflammation and fibrosis of lung tissues of rats exposed to silica particles. Metformin significantly reduced silica particle-induced inflammatory cytokines including transforming growth factor-β1 (TGF-β1), tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) in rat lung tissue and HBEC culture supernatant. The protein levels of Vimentin and α-smooth muscle actin (α-SMA) were significantly decreased by metfomin while expression level of E-cadherin (E-Cad) increased. Besides, metformin increased the expression levels of phosphorylated adenosine 5’-monophosphate (AMP)-activated protein kinase (p-AMPK), microtubule-associated protein (MAP) light chain 3B (LC3B) and Beclin1 proteins, and reduced levels of phosphorylated mammalian target of rapamycin (p-mTOR) and p62 proteins in vivo and in vitro. These results suggest that metformin could inhibit silica-induced pulmonary fibrosis by activating autophagy through the AMPK-mTOR pathway.